Income Self-Sufficiency and Profitability of Professional Theatres in the Czech Republic - Jiří Bečica (Review of Economic Perspectives, 2018)
The paper assesses the professional theatres operating under the Association of Professional Theatres in the Czech Republic in the period 2011-2015 using the financial analysis, particularly the profitability indicator ratio (ROA, ROCE, ROE, ROS) and the rate of income self-sufficiency. The reason for this economic exploration of theatres is in the fact that the service they provide fall under collectively provided public goods (a common feature of most cultural institutions), and that the market is not able to effectively secure these goods on the profit principle. The J. K. Tyl Theatre in Pilsen, the Drak Theatre in Hradec Králové and the Moravian Slovakia Theatre in Uherské Hradiště have reported the best results of profitability indicators. Whereas the worst results in profitability have been reported for the North Bohemian Theatre of Opera and Ballet in Ústí nad Labem, the Antonín Dvořák Theatre in Příbram and the South Bohemian Theatre in České Budějovice. The rate of income self-sufficiency within 2011-2015 ranges from 12-55% of the total budget volume, and volume and shows a strong dependency of professional theatres on foreign resources, particularly from public resources of the local levels of the government being the most common funder of these cultural institutions. It turns out that, from the economic point of view, it is illogical to transform non-profit contributory organizations in culture with a public funder into a different legal form when the purpose of the establishment and the funder remain preserved. Better results are generally obtained from single-genre theatres and, in terms of the auditorium size, smaller theatres focusing on drama or children's production.
Keywords: 330; culture; income self-sufficiency; profitability; theatre